Pengaruh Profitabilitas terhadap Pengeluaran Zakat di Bank-Bank Islam - Nunung Nurlaela; Amsy Eka Hasmarita (At-Tauzi : Jurnal Ekonomi Islam, 2016)
Islamic banks have used zakat instruments as a measure of company performance. It is important to know the effect of zakat on financial performance in terms of profitability ratio of Return on Assets (ROA) and Return on Equity (ROE) on Islamic banks. This research uses quantitative methods with purposive sampling. The sample was chosen from four major Islamic banks in Indonesia. The research data obtained from secondary data in the form of annual reports with the independent variable used is financial performance, namely Return on Assets (ROA) and Return on Equity (ROE), while the dependent variable is zakat.The analytical method used is the Classic Assumption Test, Multiple Linear Regression, and Hypothesis Testing. The results showed that the profitability ratio measured from ROA and ROE together, had a significant effect on zakat expenditure of 34.8%. Furthermore, the results of this study indicate that Return on Assets (ROA) has a positive effect on the zakat variable, but Return on Equity (ROE) has no effect.